2013
DOI: 10.1097/meg.0b013e32835f4c3d
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver concordance in controlled attenuation parameter measurement, a novel tool for the assessment of hepatic steatosis on the basis of transient elastography

Abstract: The determination of HS by means of CAP in HIV and/or hepatitis virus infection represents an observer-independent and easily performable method. However, the use of cut-off values for the classification of patients is suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…Sasso et al [4] studied the intraobserver reproducibility of CAP measurements and found that the method is highly reproducible, with a coefficient of variation of 4.5 %. A recently published study assessed the interobserver reproducibility of CAP measurement in a smaller series of subjects, more than half infected with the human immunodeficiency virus, and found results similar to ours [12]. Strengths of our study are the large sample size and the lack of missing data.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Sasso et al [4] studied the intraobserver reproducibility of CAP measurements and found that the method is highly reproducible, with a coefficient of variation of 4.5 %. A recently published study assessed the interobserver reproducibility of CAP measurement in a smaller series of subjects, more than half infected with the human immunodeficiency virus, and found results similar to ours [12]. Strengths of our study are the large sample size and the lack of missing data.…”
Section: Discussionsupporting
confidence: 78%
“…Data on the reproducibility of CAP measurements are few. Only one study has assessed the interobserver concordance of the CAP in patients with HIV or hepatitis virus infection [12]. To the best of our knowledge, no data obtained in consecutive patients referred for ultrasound examination and healthy volunteers are available.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that CAP is a reproducible tool for steatosis assessment and that higher BMI does not adversely affect the repeatability of the measurements [22]. Our results show that measurement of CAP is a valid method for noninvasive assessment of NAFLD, showing a correlation with other indirect markers of NAFLD and a good correlation with MRI, which gives a direct estimate of the fat in the liver.…”
Section: Discussionsupporting
confidence: 60%
“…had a long time interval of up to 17 months between liver biopsy and CAP measurement, which may have affected the hepatic steatosis assessments in this study. The intervals between liver biopsy and CAP measurement were unclear in four studies . The mean durations between CAP and liver biopsy for other studies were 26.4 days (range, 0–90 days).…”
Section: Resultsmentioning
confidence: 95%